Production of ß-glucan enriched flour from waxy barley. (May 2020) - Messia, Maria Cristina; De Arcangelis, Elisa; Candigliota, Tiziana; Trivisonno, Maria Carmela; Marconi, Emanuele
Abstract: Starch (total, amylose and amylopectin), β-glucans (total, soluble and insoluble) and pasting properties of waxy and normal barley genotypes were assessed. Waxy genotypes showed higher β-glucans content, lower starch amount and higher viscosity than normal genotypes. The USA2 waxy genotype characterized by higher β-glucans content, has been subjected to dehulling, pearling, and pin-milling and then to air classification to obtain an enriched flour that showed higher dietary fiber (23.4% d.w.) and β-glucans content (15.3% d.w.) The obtained enriched flour could be used for the production of functional foods (pasta, bread, biscuits etc) that satisfy the requirements of FDA and EU Regulation. Graphical abstract: Image 1 Highlights: Waxy barleys genotypes showed higher β-glucans content, lower starch amount and higher viscosity than normal genotypes. Waxy barley is an interesting and suitable cereal for the enrichment of bioactive compounds. β-Glucans enriched flour by air classification could be a good ingredient for functional foods preparation.